(untitled) (Desenvolvimento em Questão, 2024)
Tourism is a great means to further communities – however, if it is inadequately and unconsciously planned, it can not only harm the environment but also guarantee of future generations. Thus, sustainable development is a viable alternative, especially in tourism. Therefore, the general objective of this study was to comprehend the tourism sustainability of Trilha dos Santos Mártires das Missões as a potential tourist route and to establish connections with the dimensions of sustainability. It is worth mentioning that the understanding of sustainable development comes from the comprehension of the five dimensions of sustainability: environmental, social, territorial, economic, and political – such definitions were developed by Sachs (2004). Moreover, this study aims presenting a correlation with the dimensions of tourism sustainability. The potential of TSMM as a tourist route was elaborated in this study through the link between tourism and sustainable development.